SINTESIS SELULOSA ASETAT DARI TANDAN KOSONG KELAPA SAWIT DAN SIFATNYA SEBAGAI MEMBRAN POLIMER ELEKTROLIT PADA BATERAI ION LITIUM - Nurhadini Nurhadini; I Made Arcana (JURNAL KIMIA MULAWARMAN, 2018)
Biodegradable polymer electrolyte utilization on lithium ion battery is increasingly considered to prevent any waste. This study was conducted to synthesis cellulose acetate from oil palm empty fruit bunch and its properties as polymer electrolyte membranes on lithium ion battery. This study was done by extracting cellulose from oil palm empty fruit bunch. That cellulose was acetylated become cellulose acetate and characterized its functional group. Further, polymer electrolyte was synthesized with composition 25/60/15(%b/b) (SAS/PEO/LiClO4). The properties of polymer electrolyte membranes were characterized by analysis thermal properties, ionic conductivity and mechanical properties. Based on functional group data, synthetic cellulose acetate had similar the main functional group with commercial cellulose acetate. Synthetic cellulose acetate contained 27% acetyl with 1,4 substitution degree. Analysis thermal properties showed that the decomposition of SAS/PEO/LiClO4 polymer electrolyte membranes was started above 260oC. The ionic conductivity 10,81 x 10-4 S/cm of these polymer electrolyte membranes was 10,81 x 10-4 S/cm. Analysis of mechanic properties were 0,05 MPa stress, 14,23 MPa elongation and 0,35 MPa Modulus Young. SAS/PEO/LiClO4 polymer electrolyte membranes had higher ionic conductivity than SAK/PEO/LiClO4 polymer electrolyte membranes. However, SAS/PEO/LiClO4 polymer electrolyte membranes had lower thermal and mechanic properties than SAK/PEO/LiClO4 polymer electrolyte membranes.